Saint Michael the Archangel in medieval English legend - Johnson, Richard F. (Boydell & Brewer, 2005)
The cult and legends of St Michael the archangel were widespread in medieval England, and this book - the first full-length study of the subject - offers a comprehensive examination of their genesis and diffusion. Part I identifies and analyses the concerns, conflicts, and roles with which St Michael is associated, from scriptural and apocryphal literature through to the homiletic literature of the medieval period. Part II begins with a discussion of the vernacular recensions of the popular account of the archangel's earthly interventions, and goes on to survey the legendary accounts in Old English, Anglo-Norman, and Middle English of the archangel and his roles as guardian, intercessor, psychopomp, and warrior-angel follows. The Appendices contain the first English translation of the archangel's hagiographic foundation-myth; an annotated bibliographical list and motif index of textual materials relating to the archangel; and an essay on the iconographic representations of the archangel in medieval England. RICHARD F. JOHNSON is Assistant Professor of English at William Rainey Harper College.